Services and Development of Social Services of Semarang Regency in Handling With the Social Welfare Problems of Abandoned Children - Ridho Pakina; Yulies Tiena Masriani (Fakultas Hukum, Universitas Warmadewa, 2022)
This paper aims to describe the factors that cause children to be neglected, as well as the impact experienced by children who are neglected. The formulation of the problem, how is the service and guidance of the Semarang Regency Social Welfare Service in handling neglected children with social welfare problems and what are the obstacles and solutions to services and guidance in handling neglected children with social welfare problems. Research This research is a qualitative research that produces qualitative data. The data used in this study is primary data by conducting interviews and secondary data from books, journals and laws and regulations. From the results of the analysis of research findings, it can be seen that abandoned children tend not to be easy to communicate with, children tend not to want to be fostered, family motivation towards children is still lacking. The existence of abandoned children is caused by poverty, personality deviations, and internal and external factors of the child. They have their own way of life. Therefore, to overcome the problem of neglected children, it is necessary to empower potential sources of social welfare through Private Welfare Institutions/stakeholders, religious leaders, community leaders, community social workers, academics in an integrated, synergistic, collaborative and sustainable manner. The limitations of human resources and infrastructure at the Semarang Regency Social Service Office, especially the absence of a halfway house, need special attention from the Semarang Regency Regional Government.